History, Identity, and Multicultural Education: The Role of Endogamous Marriage in the Hadramaut Arab Community of Palembang - Apriana Apriana; Eka Mustika Riantina; Yusinta Tia Rusdiana (STAI Hubbulwathan Duri, 2025)
This study explores how historical practices—specifically endogamous marriage traditions within the Arab Hadramaut community in Palembang—offer valuable insights for multicultural education. It focuses on the construction of cultural identity, maintenance of social boundaries, and transmission of ancestral values in minority communities. A qualitative research design with a phenomenological approach was employed. Data were collected through in-depth interviews, participant observations, and literature reviews. The data were analyzed through reduction, presentation, and conclusion-drawing stages. Findings indicate that Arab-Malay cultural interactions in Palembang date back to the 16th–17th centuries. Despite these interactions, intermarriage remains limited due to adherence to the kaffaah principle. This principle supports endogamous marriage within the Alawiyyin lineage to preserve religious identity and maintain lineage from the Prophet. This historical continuity illustrates the community’s strategy for sustaining cultural values and identity across generations. The persistence of endogamous marriage within a multicultural context highlights the role of historical practices in shaping modern identity and social structures. These findings contribute to a deeper understanding of how minority communities negotiate cultural preservation within broader societal frameworks. This study provides a historical lens through which to enhance multicultural education. It supports the development of history and citizenship curricula that promote cultural literacy, social cohesion, and appreciation of pluralism.